Performance evaluation of asphalt concrete mixes under varying replacement percentages of natural sand - Albayati, Amjad H.; Abdulsattar, Harith (Results in engineering, 2020)
Frequently, load associated mode of failure, rutting and fatigue, are the main failure types found in some newly constructed roads within Baghdad, the capital of Iraq, and some suburban areas. The use of excessive amount of natural sand in asphalt concrete mixes which is attractive to local contractors could be one of the possible causes to the lack of strength properties of the mixes resulting in frustration in the pavement performance. In this study, the performance properties of asphalt concrete mixes with two natural sand types, desert and river sands, were evaluated. Moreover, five replacement rates of 0, 25, 50, 75, and 100% by weight of the fine aggregate finer than 4.75 mm were used. The performance properties including moisture susceptibility, resilient modulus, permanent deformation, and fatigue characteristics were evaluated using indirect tensile strength, uniaxial repeated loading and repeated flexural beam tests. Also, as a part of the research objective, the laboratory tests result were used to predict the performance using VESYS computer software. Results showed that mixes with high natural sand content (NSC) are more susceptible to moisture damage and rutting, lower resilient modulus and some improvement in fatigue resistance. Based on the obtained results, the necessity has rise to revise the current local specification for asphalt concrete which specifies the limits of natural sand content in the mixes of wearing and binder courses with 25% whereas for base course mixes no limit exist yet. •Performance was evaluated for asphalt concrete mixes containing different percentages of natural sand.•Two types of natural sand was considered, river and desert sand.•Five replacement rates were implemented for each type of sand; 0, 25, 50, 75, and 100% by weight of fine aggregate.•Vesys 5 ​W software implemented to predict the pavement performance.